The Importance of Mastering Arabic Speaking Skills in Islamic Universities - Arifin, Moh. Aziz; Adam Ibrahim, Faisal Mahmoud; Machmudah, Umi (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Speaking skills are the ability to convey ideas logically and systematically with language rules that are appropriate to the appropriate communication context. Â The importance of mastering Arabic language skills among students, especially in Islamic higher education, is evident in the reality on the ground. The curriculum in Islamic universities includes Arabic language courses in programs other than Arabic language education. This demonstrates that even students who are not majoring in Arabic education are familiar with Arabic language courses and the content of Arabic language learning. The purpose of this study is to determine the ability of Arabic speaking skills in Islamic colleges and indicators that improve Arabic speaking skills. The method used in this study is descriptive qualitative, namely by describing the data that has been obtained through the data collection process. The results of the study indicate that the ability of students in Islamic colleges is included in the category of being able and having the competence to speak Arabic, but the obstacle faced is the need for a supportive environment to speak Arabic. The most basic indicators of Arabic speaking skills are the first is the individual factor, the second is the environmental factor.